2012
DOI: 10.1152/ajpendo.00525.2011
|View full text |Cite
|
Sign up to set email alerts
|

Leucine and mTORC1: a complex relationship

Abstract: Amino acid availability is a rate-limiting factor in the regulation of protein synthesis. When amino acid supplies become restricted, mammalian cells employ homeostatic mechanisms to rapidly inhibit processes such as protein synthesis, which demands high levels of amino acids. Muscle cells in particular are subject to high protein turnover rates to maintain amino acid homeostasis. Mammalian target of rapamycin complex 1 (mTORC1) is an evolutionary conserved multiprotein complex that coordinates a network of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
185
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(196 citation statements)
references
References 114 publications
(129 reference statements)
3
185
0
8
Order By: Relevance
“…Therefore, patients with diabetes mellitus were excluded from the study. Insulin resistance results in increased proteolysis and BCAA levels are elevated [15,22]. In skeletal muscle, BCAAs act as an essential donor of nitrogen in the BCAA transaminase reaction to form glutamate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, patients with diabetes mellitus were excluded from the study. Insulin resistance results in increased proteolysis and BCAA levels are elevated [15,22]. In skeletal muscle, BCAAs act as an essential donor of nitrogen in the BCAA transaminase reaction to form glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…Also worth mentioning is a positive correlation between BCAA and TG. It is known that BCAAs contribute to insulin resistance [22]. Insulin resistance may lead to an increase of serum TG.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mTORC1 has a number of repressors, which must be dissociated from the complex to allow it to become active, such as PRAS40 and DEPTOR [94]. Finally the amino acid sensitive lipid kinase hVPS34 also plays a key role in mTORC1 activation [95] as does the MAPK family member MAP4K3 [96] ( Figure 2). Cell based work has shown that this amino acid sensing system is incredibly sensitive with an ~7% increase in intracellular leucine leading to 50% maximal activation of mTORC1 [97].…”
Section: The Molecular Regulation Of Resistance Training Adaptationmentioning
confidence: 99%
“…It has been previously reported that leucine can enhance mTORC1 (Deldicque et al 2008;Dodd and Tee 2012;Suryawan et al 2012;Xu et al 2013). To examine if the mTORC1 inhibitory effect of glutamine can be neutralized by coadministration of leucine in vivo, independent groups of rats were infused with leucine (27 mg) targeted to one hippocampus while Glutamine impairs long-term memory www.learnmem.org an equal volume of vehicle was simultaneously infused into the contralateral hippocampus.…”
Section: Memory Impairing Effect Of Glutamine Can Be Overcome By Coadmentioning
confidence: 99%